REFLEKSI DAN IMPLIKASI PENELITIAN DISERTASI DOKTOR DAN MENULIS UNTUK JURNAL INTERNASIONAL - Imroatus Solikhah (Center of Language and Cultural Studies, 2016)
This paper is for all intens and purposes to describe challanges and struggle to develop Ph.D’ research and strggle to submit articles in an internasional journal. Evaluation on reading strategies that empasize on critical reading and evaluative reading were described to support description on writing for academic context and writing for journal article. Topibs to be delivered in the paper include: Introduction, Reflection on reading competency, Trigger to write journal article, Preparing Ph.D’s field research, Preparing to submit articles for international journal, and Conclusion.